Copper Cobalt Sulfide Nanosheets Realizing a Promising Electrocatalytic Oxygen Evolution Reaction - Chauhan, Meenakshi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Catalysis, 2017)
Nanostructured CuCo2S4, a mixed metal thiospinel, is found to be a benchmark electrocatalyst for oxygen evolution reaction (OER) in this study with a low overpotential, a low Tafel slope, a high durability, and a high turnover frequency (TOF) at lower mass loadings. Nanosheets of CuCo2S4 are realized from a hydrothermal synthesis method in which the average thickness of the sheets is found to be in the range of 815 nm. Aggregated nanosheets form a highly open hierarchical structure. When used as an electrocatalyst, CuCo2S4 nanosheets offer an overpotential value of 310 mV at a 10 mA cm(2) current density, which remains consistent for 10000 measured cycles in a 1 M KOH electrolyte. A chronoamperometric study reveals constant oxygen evolution for 12 h at a 10 mV s(-1) scan rate without any degradation of the activity. Furthermore, the calculated mass activity of the CuCo2S4 electrocatalyst is found to be 14.29 A/g and to afford a TOF value of 0.1431 s(-1) at 310 mV at a mass loading of 0.7 mg cm(-2). For comparison, nanostructures of Co3S4 and Cu0.5Co2.5S4 have been synthesized using a similar method followed for CuCo2S4. When compared to the OER activities among these three thiospinels and standard IrO2, CuCo2S4 nanosheets offered the highest OER activities at the same mass loading (0.7 mg/cm(-2)). Extensive X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses for a mechanistic study reveal that introduction of Cu into the Co3S4 lattice enhances the oxygen evolution and kinetics by offering Cu2+ sites for utilitarian adsorption of OH, O, and OOH reactive species and also by offering a highly active high-spin state of octahedral Co3+ for OER catalysis.
Keywords: Bifunctional Electrocatalyst; Catalyst; Cuco2s4; Efficient Electrocatalyst; electrocatalyst; Electronic-structure; Nanoparticles; Nanosheet; oxide; oxygen evolution; performance; Recent Progress; Water oxidation; Water Splitting Hydrogen Evolution